Validity Evidence of a Scale Designed to Assess Children’s Metacognition - Pascualon-Araujo, Jussara Fatima (2015)
Thoughts and knowledge that individuals have about their own cognitive processes define the term metacognition.The aim of this work was to continue the validation process of Metacognition Scale (EMETA) analyzing evidence based onthe structure and consistency internal and a comparison between the means to investigate the influences of variables such asgender, school type and age of participants. The results found with 196 participants between 9 and 12 years old indicate thepresence of a single factor called Metacognition and the possibility to reduction for 40 items. There was no significant differenceinfluenced by the three variables. Despite the favorable results to the accumulation of evidence of validity, other parametersmust still be evaluated on future researches.